2005
DOI: 10.1074/jbc.m410292200
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Functional Reconstitution, and Characterization of the Saccharomyces cerevisiae Isoprenylcysteine Carboxylmethyltransferase Ste14p

Abstract: Numerous proteins, including Ras, contain a C-terminal CAAX motif that directs a series of three sequential post-translational modifications: isoprenylation of the cysteine residue, endoproteolysis of the three terminal amino acids and ␣-carboxyl methylesterification of the isoprenylated cysteine. This study focuses on the isoprenylcysteine carboxylmethyltransferase (Icmt) enzyme from Saccharomyces cerevisiae, Ste14p, the founding member of a homologous family of endoplasmic reticulum membrane proteins present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 48 publications
0
75
0
Order By: Relevance
“…The diffusion rate obtained for C 20 BAS was slower by a factor of five relative to POPC under the same conditions. When 30 mol% Chol was incorporated in the C 20 BAS membrane, the observed lateral diffusion rate decreased by an order of magnitude, giving a value similar to that obtained for the longer chain C 32 phytBAS derivative.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The diffusion rate obtained for C 20 BAS was slower by a factor of five relative to POPC under the same conditions. When 30 mol% Chol was incorporated in the C 20 BAS membrane, the observed lateral diffusion rate decreased by an order of magnitude, giving a value similar to that obtained for the longer chain C 32 phytBAS derivative.…”
Section: Discussionmentioning
confidence: 76%
“…The impact of bolalipid structure and membrane composition on Ste14p activity, monitored by an in vitro vapor diffusion methyltransferase assay (20), was then determined using vesicles of differing lipid composition, gel to liquid crystalline phase transition temperatures, and lipid mobility. Confocal immunofluorescence microscopy and protein assays were used to determine the extent and distribution of Ste14p in reconstituted vesicle membranes.…”
mentioning
confidence: 99%
“…Because of its membrane spans and because it lacks a classical methyltransferase consensus motif, Icmt is an atypical member of the methyltransferase family of enzymes 40 . However, the recent purification of Ste14p from yeast, and its reconstitution in liposomes in an enzymatically active form, have provided conclusive evidence that it is the sole component comprising Icmt activity 40,41 . Using the purified enzyme, researchers showed that yeast Ste14p recognizes the farnesylated and geranylgeranyl substrates N-acetyl-S-farnesylcysteine and N-acetyl-S-geranylgeranylcysteine equivalently.…”
Section: Enzymatic Processing Of Prenylated Proteinsmentioning
confidence: 99%
“…Given the importance of carboxyl methylation for Ras-induced onco-genesis shown by the Icmt mouse studies mentioned above, the development of Icmt inhibitors as anticancer drugs is of obvious interest 19,41,47 . The well-known chemotherapeutic compound methotrexate (an antifolate that blocks thymidine synthesis, which is necessary for tumor growth) causes accumulation of S-adenosylhomocysteine, a potent inhibitor of nearly all cellular methyltransferases; it has been suggested that at least some of methotrexate's antitumor activity may stem from its ability to inhibit Icmt, though specificity for Icmt is lacking 48 .…”
Section: Enzymatic Processing Of Prenylated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation